Cover Image, Volume 75, Issue 12. Issue 12 (6th November 2019) - Zhu, Xiang; Yu, Linhua; Hsiang, Tom; Huang, Di; Xu, Zhihong; Wu, Qinglai; Du, Xiaoying; Li, Junkai
Abstract : The cover image is based on the Original Article The influence of steric configuration of phenazine‐1‐carboxylic acid‐amino acid conjugates on fungicidal activity and systemicity by Xiang Zhu et al., https://doi.org/10.1002/ps.5455 . Abstract : The cover image is based on the Original Article The influence of steric configuration of phenazine‐1‐carboxylic acid‐amino acid conjugates on fungicidal activity and systemicity by Xiang Zhu et al., https://doi.org/10.1002/ps.5455 .